Decision Support System For Work Training Selection At Department Of Labor Asahan AHP Method - Yunika Afrianti; William Ramdhan; Wan Mariatul Kifti (Yayasan Cita Cendekiawan Al Khwarizmi, 2026)
The increasingly rapid development of information technology has significantly impacted various sectors, including the government sector. One area of government that greatly requires information technology support is the management of job training programs organized by the Asahan Regency Manpower Office. In its implementation, the number of job training applicants often exceeds the available quota, necessitating an appropriate Decision Support System process. The AHP method is a multi-criteria decision-making method capable of breaking down complex problems into a hierarchical structure consisting of objectives, criteria, and alternatives. However, to date, no systematic analysis has been conducted on the selection of training applicants. This study aims to apply the Analytical Hierarchy Process (AHP) method to a Decision Support System as a basis for prioritizing job training participants based on predetermined criteria. The data used in this study include prospective job training participants and the assessment criteria used by the Asahan Regency Manpower Office, such as education, age, work experience, and income. Data were collected through observation, interviews, and literature review using a decision support system approach. The results of this study indicate that Nurhayati received the highest Preference Score (Yi) of 0.8462, placing her in first place, followed by Andi Saputra with a Preference Score (Yi) of 0.8157 and Dewi Sartika with a Preference Score (Yi) of 0.7620. The conclusion of this study is that the application of the Analytical Hierarchy Process (AHP) method can significantly contribute to accurate decision-making.